2008
DOI: 10.1097/mbc.0b013e328309905d
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin acts on platelets to generate procoagulant activity

Abstract: The aim of our study was to examine whether arginine vasopressin (AVP) is able to evoke in human platelets a procoagulant response due to activation of an Na+/H+ exchanger. It was found that treatment of platelets with AVP (20-100 nmol/l) results in generation of a weak calcium signal, activation of Na+/H+ exchanger, aggregation, and development of a procoagulant response. The AVP-evoked procoagulant response was dose and time dependent, weaker than that produced by collagen or monensin (mimics Na+/H+ exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Vasopressin and the renin-angiotensin system are important after hemorrhage as they affect blood pressure and volume; however, they may also influence hemostatic competence. Vasopressin elevates the expression of phosphatidylserine on platelet surfaces and enhances thrombin generation [24] , and increases fibrinolysis by elevating plasma t-PA [25] . In the present study, however, vasopressin did not differ from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin and the renin-angiotensin system are important after hemorrhage as they affect blood pressure and volume; however, they may also influence hemostatic competence. Vasopressin elevates the expression of phosphatidylserine on platelet surfaces and enhances thrombin generation [24] , and increases fibrinolysis by elevating plasma t-PA [25] . In the present study, however, vasopressin did not differ from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…V1AR has been shown to be involved in many cellular processes including vascular contraction as well as in the metabolism of glucose, lipids, and protein [38]. Additionally, studies using V1AR knockout mice and isolated cells showed that the V1AR regulates glucose homeostasis [39], mediates the release of aldosterone from adrenal gland cells [38, 40], controls social interactions [41], and platelet aggregation [42, 43]. V1BR mediates the release of adrenocorticotropic hormone and insulin from the pituitary gland and islet cells of the pancreas, respectively [38, 44].…”
Section: Physiologic and Cellular Consequences Of Avp Receptor Sigmentioning
confidence: 99%
“…Both ions (sodium and calcium) have been recognized as crucial factors during platelet swelling, ballooning (forming of a balloon-shaped morphology of particularly strongly procoagulant platelets), and PS exposure in platelets adhered to collagen [ 42 ]. NHE plays a pivotal role in controlling platelet swelling—a phenomenon correlating with platelet ballooning and PS exposure [ 29 , 42 , 56 , 57 , 59 , 60 ]—by generation of an osmotic gradient, driving water molecules into platelet cytosol via aquaporins (AQPs). Previously, we reported enhanced ballooning of platelets adhered to collagen after preincubation with adrenaline [ 15 ].…”
Section: Discussionmentioning
confidence: 99%